Effects of a healthy Nordic diet on cardiovascular risk factors in hypercholesterolaemic subjects: a randomized controlled trial (NORDIET) - Adamsson, V.; Reumark, A.; Fredriksson, I.‐B.; Hammarström, E.; Vessby, B.; Johansson, G.; Risérus, U. (Journal of internal medicine, 2011)
.  Adamsson V, Reumark A, Fredriksson I‐B, Hammarström E, Vessby B, Johansson G, Risérus U (Uppsala University, Uppsala; Lantmännen R&D, Stockholm; Bollnäs Heart Clinic, Mitt Hjärta, Bollnäs; Halmstad University, Halmstad, Sweden). Effects of a healthy Nordic diet on cardiovascular risk factors in hypercholesterolaemic subjects: a randomized controlled trial (NORDIET). J Intern Med 2011; 269: 150–159. Objective.  The aim of this study was to investigate the effects of a healthy Nordic diet (ND) on cardiovascular risk factors. Design and subjects.  In a randomized controlled trial (NORDIET) conducted in Sweden, 88 mildly hypercholesterolaemic subjects were randomly assigned to an ad libitum ND or control diet (subjects’ usual Western diet) for 6 weeks. Participants in the ND group were provided with all meals and foods. Primary outcome measurements were low‐density lipoprotein (LDL) cholesterol, and secondary outcomes were blood pressure (BP) and insulin sensitivity (fasting insulin and homeostatic model assessment‐insulin resistance). The ND was rich in high‐fibre plant foods, fruits, berries, vegetables, whole grains, rapeseed oil, nuts, fish and low‐fat milk products, but low in salt, added sugars and saturated fats. Results.  The ND contained 27%, 52%, 19% and 2% of energy from fat, carbohydrate, protein and alcohol, respectively. In total, 86 of 88 subjects randomly assigned to diet completed the study. Compared with controls, there was a decrease in plasma cholesterol (−16%, P < 0.001), LDL cholesterol (−21%, P < 0.001), high‐density lipoprotein (HDL) cholesterol (−5%, P < 0.01), LDL/HDL (−14%, P < 0.01) and apolipoprotein (apo)B/apoA1 (−1%, P < 0.05) in the ND group. The ND reduced insulin (−9%, P = 0.01) and systolic BP by −6.6 ± 13.2 mmHg (−5%, P < 0.05) compared with the control diet. Despite the ad libitum nature of the ND, body weight decreased after 6 weeks in the ND compared with the control group (−4%, P < 0.001). After adjustment for weight change, the significant differences between groups remained for blood lipids, but not for insulin sensitivity or BP. There were no significant differences in diastolic BP or triglyceride or glucose concentrations. Conclusions.  A healthy ND improves blood lipid profile and insulin sensitivity and lowers blood pressure at clinically relevant levels in hypercholesterolaemic subjects.